Artificial intelligence for photonics and photonic materials. (18th December 2020) - Piccinotti, Davide; MacDonald, Kevin F; A Gregory, Simon; Youngs, Ian; Zheludev, Nikolay I
Abstract: Artificial intelligence (AI) is the most important new methodology in scientific research since the adoption of quantum mechanics and it is providing exciting results in numerous fields of science and technology. In this review we summarize research and discuss future opportunities for AI in the domains of photonics, nanophotonics, plasmonics and photonic materials discovery, including metamaterials.